Hybrid Drying Method: Influence of Pre-Treatment and Process Conditions of Ultrasound-Assisted Drying on Apple Quality - Aleksandra Jedlińska; Katarzyna Rybak; Katarzyna Samborska; Alicja Barańska-Dołomisiewicz; Aleksandra Skarżyńska; Magdalena Trusińska; Dorota Witrowa-Rajchert; Małgorzata Nowacka (Applied Sciences)
Ultrasound (US) is a non-thermal food processing method that can be used as a pre-treatment or integrated during drying to enhance mass transfer by inducing cavitation and forming microchannels in plant tissue. Thus, this study investigated the combined effect of ultrasound pre-treatment (21 kHz; 180 W; 10 min, 20 min, 30 min) and the subsequent hybrid drying process—ultrasound-assisted hot-air drying (temperature of 70 °C, frequency of 36 kHz; ultrasound power of 120 W, 160 W, 200 W)—on the drying kinetics and quality attributes of dried Gloster apples. The experimental design was optimized using the response surface methodology (RSM). The effects of ultrasound parameters on drying time, dry matter content, water activity, rehydration and hygroscopic properties, color change, textural properties, content of vitamin C, polyphenols and flavonoids, and antioxidant activity were evaluated. Among the analyzed variants, the most effective combinations were longer US duration (30 min) with lower US power (120 W) or shorter US duration (10 min) with higher US power (200 W). To obtain dried material with the most desirable rehydration and hygroscopic properties, a US power in the range of 120–160 W, preceded by a US pre-treatment lasting 20 min, should be selected. Conversely, optimizing the content of bioactive components would involve choosing the longest US treatment time and medium to high ultrasonic power during drying. These results provide actionable insights for the industry to tailor drying parameters based on the desired product attributes.